2004
DOI: 10.1001/jama.291.19.2335
|View full text |Cite
|
Sign up to set email alerts
|

Recovery and Long-term Function After Hematopoietic Cell Transplantation for Leukemia or Lymphoma

Abstract: URVIVAL RATES AFTER MYELOABlative hematopoietic cell transplantation (HCT) have improved considerably during the past 30 years. 1 The growing population of patients who have survived this treatment has intensified the need to determine the course of recovery and to identify risk factors for less favorable functional outcomes. Improved understanding of recovery will facilitate more accurate informed consent, permit better planning by patients, families, and medical teams, and enable the design of interventions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

24
380
13
7

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 311 publications
(424 citation statements)
references
References 34 publications
(36 reference statements)
24
380
13
7
Order By: Relevance
“…Because of differences in study designs, as outlined in the Introduction section, it is difficult to compare studies. The RTW rate in the present study was 81%, when based only on those working before SCT, which is lower 18,19 or higher 21 than results from studies calculating the RTW rate in this way (Table 6). The proportion that reduces their working time after a cancer diagnosis varies, 31 and the same pattern is seen in the very few studies that report on part-time work among SCT survivors.…”
Section: Discussioncontrasting
confidence: 70%
See 3 more Smart Citations
“…Because of differences in study designs, as outlined in the Introduction section, it is difficult to compare studies. The RTW rate in the present study was 81%, when based only on those working before SCT, which is lower 18,19 or higher 21 than results from studies calculating the RTW rate in this way (Table 6). The proportion that reduces their working time after a cancer diagnosis varies, 31 and the same pattern is seen in the very few studies that report on part-time work among SCT survivors.…”
Section: Discussioncontrasting
confidence: 70%
“…7,16,17 Prospective studies including both autologous and allo-SCT patients show that RTW improves gradually from 1 to 5 years post SCT. 18,19 At 10 years, allo-SCT patients exhibit similar levels of working full-time when compared with healthy case-matched controls (72% vs 74%). 8 However, there are several methodological problems with previous studies investigating RTW in SCT patients.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…4,5 Despite these strategies, 30-40% of patients develop acute and chronic GVHD, which not only result in morbidity and mortality but also have a negative impact on the quality of life. [4][5][6][7] Unlike hematologic malignancies, GVHD probably has no therapeutic benefit in patients with AA and prevention of GVHD is one of the most desirable goals of BMT in AA. Previous studies from St George's Hospital in London reported a favorable effect on acute and chronic GVHD in matched sibling donor and matched unrelated donor BMT for AA using in vivo anti-CD52 monoclonal antibodies (Campath-1G antibodies and alemtuzumab).…”
Section: Introductionmentioning
confidence: 99%